EKSPLORASI PENGELOLAAN RUANG PUBLIK GALERI INDONESIA KAYA SEBAGAI PUSAT EDUKASI-HIBURAN DAN DAYA TARIK WISATA - Hanorsian, Anastasia Enike; Suharto, Bambang; Isnaini, Santi (Kepariwisataan: Jurnal Ilmiah, 2024)
The Galeri Indonesia Kaya in Jakarta is a unique public space that uses digital technology to blend cultural education and interactive entertainment. This study investigates the management of this gallery as an urban tourist attraction with a focus on its educational and entertaining approach. The research aims to explore the management model of the Galeri Indonesia Kaya, assess the effectiveness of integrating education and entertainment concepts, and analyze its impact on urban tourism. Through a qualitative case study methodology, data was gathered using observation, interviews, and document analysis. The analysis revealed six main elements of management: regulation, maintenance, investment, coordination, social participation, and preservation of local culture and identity. Despite challenges in maintaining technology, the findings demonstrate that the gallery successfully balances educational and entertainment aspects through seven digital art attractions. The gallery serves as a vital public education platform and promotes positive social interaction in Jakarta. This study contributes to developing a model for managing cultural public spaces in the digital age, emphasizing the gallery's potential as an innovative example in preserving and promoting Indonesian culture. The research provides valuable insights for policymakers and cultural managers on integrating technology into cultural preservation and urban tourism development.